Resistance to surface active drugs of wild type strains and newly isolated mutants of Neurospora crassa. - A. Al-Saqur; B. R. Smith (Fungal Genetics Reports, 1980)
Resistance to surface active drugs of wild type strains and newly isolated mutants of Neurospora crassa.